EVALUATION OF CERES-MAIZE MODEL FOR HYBRID MAIZE (Zea mays L.) PRODUCTION - Amied Ali; Bashrat Ali (AGRIBUSINESS JOURNAL, 2019)
The trial was conducted at Agronomic Research farm, University of Sargodha during spring growing season, 2015, to calibrate and evaluate CERES-Maize model for simulating the impact of different sowing time on maize crop. The experiment was laid out in split plot design having three replications, keeping planting dates (25th Feb, 6thMar and 14thMar) in main plots and hybrids i.e. (DK-9108, DK-6525 and DK-6142) in the sub plots. The Calibration of CSM-CERES-Maize model showed the best possible closeness between simulated and observed days to flowering and physiological maturity, leaf area index (LAI), Total dry matter (TDM), and grain yield with % error of 4.0, -1.5, 0.41, 0.07, 0.14 and 0.3% , respectively, when maize hybrid H1 (DK- 6142) was sown at firstsowing date (25th Feb). DSSAT,CERES- Maize model predicted the phenological traits like anthesis and maturity phase. Number of days to anthesis and maturity simulated by model were lesser to the observed values, where as, simulated grain yield was higher as compared to observed data for all the three cultivars. Model calculated the close similarity between experimental and computer-generated values for leaf area index.